2008
DOI: 10.1029/2007ja012362
|View full text |Cite
|
Sign up to set email alerts
|

Pc1–Pc2 waves and energetic particle precipitation during and after magnetic storms: Superposed epoch analysis and case studies

Abstract: Magnetic pulsations in the Pc1–Pc2 frequency range (0.1–5 Hz) are often observed on the ground and in the Earth's magnetosphere during the aftermath of geomagnetic storms. Numerous studies have suggested that they may play a role in reducing the fluxes of energetic ions in the ring current; more recent studies suggest they may interact parasitically with radiation belt electrons as well. We report here on observations during 2005 from search coil magnetometers and riometers installed at three Antarctic station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
146
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(166 citation statements)
references
References 63 publications
(115 reference statements)
15
146
3
Order By: Relevance
“…Most events had frequencies between 0.2 and 1.4 Hz. The distribution of frequencies observed by ST5 is qualitatively similar to that shown in Figure 8 of Engebretson et al [2008], which grouped frequencies observed at Halley, Antarctica ( L = 4.56), according to UT and day after magnetic storm onset. Figure 9 (middle) shows the distribution of wave frequencies as a function of amplitude (from 5 to 110 nT); these show no evident correlation.…”
Section: Occurrence Patternssupporting
confidence: 74%
See 1 more Smart Citation
“…Most events had frequencies between 0.2 and 1.4 Hz. The distribution of frequencies observed by ST5 is qualitatively similar to that shown in Figure 8 of Engebretson et al [2008], which grouped frequencies observed at Halley, Antarctica ( L = 4.56), according to UT and day after magnetic storm onset. Figure 9 (middle) shows the distribution of wave frequencies as a function of amplitude (from 5 to 110 nT); these show no evident correlation.…”
Section: Occurrence Patternssupporting
confidence: 74%
“…Pc1–2 wave activity has also been suggested as a possible prompt loss mechanism for relativistic electrons during the main phase of such storms [ Thorne et al , 2005]. However, although the few published satellite studies of Pc1–2 waves during storms report their occurrence during both main and recovery phases, such waves are consistently absent in ground data during the main and early recovery phases [e.g., Bräysy et al , 1998; Engebretson et al , 2008].…”
Section: Relation To Magnetic Stormsmentioning
confidence: 99%
“…At present there is a peculiarity that most MeV electron loss in the radiation belts occurs during main phase, yet on the ground EMIC power typically only appears during the recovery phase (e.g. Engebretson et al 2008;Bortnik et al 2008 and references therein). Whether this is due to internal reflection of EMIC waves in the magnetosphere (e.g.…”
Section: Electromagnetic Ion Cyclotron (Emic) Wavesmentioning
confidence: 97%
“…In fact, there is still much current interest in ion pitch angle scattering by EMIC waves in the context of ring current dynamics. This is evidenced by the substantial literature that relates EMIC waves to ion precipitation resulting in ring current decay [e.g., Cornwall et al, 1970;Erlandson and Ukhorskiy, 2001;Summers, 2005;Fraser et al, 2006;Jordanova et al, 2007;Yahnin and Yahnina, 2007;Engebretson et al, 2008;Sakaguchi et al, 2008;Spasojevic et al, 2011;Xiao et al, 2012;Yuan et al, 2014]. In the present work, we treat EMIC wave-ion interactions as linear or quasi-linear, in common with most previous studies.…”
Section: Introductionmentioning
confidence: 69%